Analysis of Information Technology Proficiency Levels For Academic Services Using The Cobit 2019 Framework: Case Study of SMP Negeri 102 Jakarta - Ismiyati Meiharsiwi; Gerry Firmansyah; Agung Mulyo Widodo; Budi Tjahjono (Asian Journal of Social and Humanities, 2024)
This research intends to analyze the level of capability of information technology (IT) in academic services at SMP Negeri 102 Jakarta using the COBIT 2019 framework. The background of this research is the important role of information technology in increasing the efficiency and effectiveness of the learning process in educational institutions. COBIT 2019 was chosen as a framework because it is a best practice in IT governance that can help institutions achieve their strategic goals. This research focuses on the IT governance process implemented at SMP Negeri 102 Jakarta, the maturity level of existing information system governance, and recommendations for improving IT governance. The case study method is used with limitations on the domain within Align, Place and Organize (APO) 09 dan Deliver, Service and Support (DSS) 01 the COBIT 2019 framework. Research findings show that IT governance at SMP Negeri 102 Jakarta is at a certain level of capability that needs to be improved. This research provides recommendations for improving academic services through improving IT governance. It is hoped that the results of this research can become a reference in determining IT policies at SMP Negeri 102 Jakarta and contribute to the development of knowledge in the field of information technology governance.